Efficiency, Participation, and Quality: Three Dimensions of E-Government?. (August 2015) - Gable, Matt
This book review essay offers a picture of e-government scholarship that involves three major themes: efficiency, citizen participation, and quality. Two of the themes, efficiency and citizen participation, have sometimes been counterposed in public administration literature, seeing citizen participation coming at the expense of efficiency. In this essay, the effects of the goals of efficiency and citizen participation on the third theme, "quality" in e-government literature, are explored via a thematic map based on multidimensional scaling. This analysis offers that efficiency and political participation in e-government literature stem from macro-political conceptions, and they are separate from "quality" concerns.